Young People's Joint Leisure Activities in Traditional Karelian Culture: Norms and Social Practice - Valentina Mironova; Julia Litvin (Journal of Ethnology and Folkloristics)
The paper considers common youth leisure activities in traditional Karelian culture, from the point of view both of the culturally prescribed norms and the actual behaviour. Special attention is paid to official and social adolescent development frameworks and to reflection of these age-related stages in folk vocabulary. The paper uses a large number of recently published and unpublished ethnographic and folkloristic sources. The authors come to the conclusion that in Karelian culture there is a specific age-group framework for adolescence, as well as gender-related differences between male and female behavioural patterns. The paper shows that girls had to undertake more varied tasks than boys as, on the one hand, they were to play socially prescribed roles and follow moral obligations, remaining modest and, on the other hand, had to be active in order to get married and give birth to children.